Fabry Nephropathy: An Evidence-Based Narrative Review - María del Pino; Amado Andrés; Ana Ávila Bernabéu; Joaquín de Juan-Rivera; Elvira Fernández; Juan de Dios García Díaz; Domingo Hernández; José Luño; Isabel Martínez Fernández; José Paniagua; Manuel Posada de la Paz; José Carlos Rodríguez-Pérez; et al. (Karger Publishers, 2018)
Fabry disease (FD) is a rare, X-linked disorder caused by mutations in the GLA gene encoding the enzyme α-galactosidase A. Complete or partial deficiency in this enzyme leads to intracellular accumulation of globotriaosylceramide (Gb3) and other glycosphingolipids in many cell types throughout the body, including the kidney. Progressive accumulation of Gb3 in podocytes, endothelial cells, epithelial cells, and tubular cells contribute to the renal symptoms of FD, which manifest as proteinuria and reduced glomerular filtration rate leading to renal insufficiency. A correct diagnosis of FD, although challenging, has considerable implications regarding treatment, management, and counseling. The diagnosis may be confirmed by demonstrating the enzyme deficiency in males and by identifying the specific GLA gene mutation in male and female patients. Treatment with enzyme replacement therapy, as part of the therapeutic strategy to prevent complications of the disease, may be beneficial in stabilizing renal function or slowing its decline, particularly in the early stages of the disease. Emergent treatments for FD include the recently approved chaperone molecule migalastat for patients with amenable mutations. The objective of this report is to provide an updated overview on Fabry nephropathy, with a focus on the most relevant aspects of its epidemiology, diagnosis, pathophysiology, and treatment options.